2008
DOI: 10.2527/jas.2008-0924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplemental energy source and frequency on growing calf performance1

Abstract: Crossbred heifers (n = 120; 265 kg, SD = 37) were fed individually (84 d) to determine the effect of supplement type, concentration, and frequency on intake and performance and to estimate the energy value of dry distillers grains plus solubles (DDGS) in a high-forage diet. Treatments were arranged in a 3 × 2 × 2 factorial, with 3 supplements, 2 concentrations, and 2 frequencies of supplementation. Supplements including dry-rolled corn (DRC), DRC with corn gluten meal (DRC + CGM), and DDGS were fed at 0.21% (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 27 publications
5
34
0
1
Order By: Relevance
“…Changes in the grazing behavior of animals receiving supplements at a lower frequency were observed by Pulido et al (2009) and Loy et al (2008). Based on these studies, infrequent supplementation may alter the feeding behavior of animals, which may lead to a lower intake of pasture DM.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Changes in the grazing behavior of animals receiving supplements at a lower frequency were observed by Pulido et al (2009) and Loy et al (2008). Based on these studies, infrequent supplementation may alter the feeding behavior of animals, which may lead to a lower intake of pasture DM.…”
Section: Introductionmentioning
confidence: 74%
“…However, if the frequency of supply of concentrate supplements is reduced to three times weekly, animals may display lower weight gains (ARTIOLI et al, 2015;COOKE et al, 2008;LOY et al, 2008). According to Cooke et al (2008), decreasing the frequency of energy supplementation to three times per week reduced the performance of beef heifers reared on pasture during the rainy season by 18%.…”
Section: Introductionmentioning
confidence: 99%
“…Success of less frequent supplementation of energy based supplements may at least partially depend on availability of ruminal N for efficient microbial growth and digestion. Loy et al (2008) showed that the effects of supplementation frequency on gains of heifers consuming medium quality hay tended to differ depending on the source of protein used in the energy supplement. Hay intake was decreased but gains were not negatively affected by reducing supplementation frequency to 3 times a week when a supplement high in ruminally degradable protein (dry rolled corn plus urea) was fed.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the heifers supplemented with dry rolled corn and urea 3X had a greater gain to feed ratio than those supplemented daily in their study. Additionally, the purine derivative to creatinine ratio in the urine was greater for heifers supplemented with dry rolled corn plus urea 3X than those supplemented daily suggesting that heifers supplemented 3X absorbed more microbial protein (Loy et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…A mudança na frequência de suplementação tem sido estudada internacionalmente (BOHNERT et al, 2002;LOY et. al., 2008) e pode ser uma opção eficiente para reduzir tempo, trabalho e equipamentos relativos ao fornecimento de suplementos, sem causar I Programa de Pós-graduação em Zootecnia, Universidade Federal de Santa Maria (UFSM), Santa Maria, RS, Brasil.…”
Section: Introductionunclassified